2021
DOI: 10.3174/ajnr.a6960
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Degree of Dopaminergic Denervation Based on the Loss of Nigral Hyperintensity on SMWI in Parkinsonism

Abstract: BACKGROUND AND PURPOSE: Nigrostriatal dopaminergic function in patients with Parkinson disease can be assessed using 123 I-2b -carbomethoxy-3b -(4-iodophenyl)-N-(3-fluoropropyl)-nortropan dopamine transporter ( 123 I-FP-CIT) SPECT, and a good correlation has been demonstrated between nigral status on SWI and dopaminergic denervation on 123 I-FP-CIT SPECT. Here, we aim to correlate quantified dopamine transporter attenuation on 123 I-FP-CIT SPECT with nigrosome-1 status using susceptibility map-weighted imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
1
6
1
Order By: Relevance
“…16 A direct comparison of SMWI to standard SWI in the assessment of DNH resulted in a superiority of SMWI in terms of a higher interobserver agreement, a higher concordance rate with 123 I-FP-CIT SPECT and a higher diagnostic performance for PD. 17 Therefore, our results and the findings of previous studies using more advanced SWI techniques [16][17][18][19] emphasize the importance of appropriate technical standards to ensure a sufficient diagnostic accuracy of DNH in neurodegenerative parkinsonism. Particularly important in imaging the SN are a sufficient spatial resolution, the slice thickness and the signal-to-noise-ratio (SNR).…”
Section: Discussionsupporting
confidence: 58%
“…16 A direct comparison of SMWI to standard SWI in the assessment of DNH resulted in a superiority of SMWI in terms of a higher interobserver agreement, a higher concordance rate with 123 I-FP-CIT SPECT and a higher diagnostic performance for PD. 17 Therefore, our results and the findings of previous studies using more advanced SWI techniques [16][17][18][19] emphasize the importance of appropriate technical standards to ensure a sufficient diagnostic accuracy of DNH in neurodegenerative parkinsonism. Particularly important in imaging the SN are a sufficient spatial resolution, the slice thickness and the signal-to-noise-ratio (SNR).…”
Section: Discussionsupporting
confidence: 58%
“…Many previous studies have demonstrated the high diagnostic performance of SMwI in assessing nigral hyperintensity [ 8 12 16 17 18 ]. However, most previous studies were conducted with varying imaging protocols, and presented conflicting assumptions regarding the optimal imaging plane for assessing nigral hyperintensity [ 9 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown the high diagnostic performances of both SWI and SMwI in determining the nigral hyperintensity in the substantia nigra [ 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 ]. However, these studies used heterogeneous study populations and imaging protocols, and discretionally chose different types of MR acquisition planes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent 123 I‐FP‐CIT single photon emission computed tomography (SPECT) study reported a similar degree of dopamine denervation required for the loss of nigral hyperintensity on SMwI in PD patients [28]. The researchers enrolled patients with frontal gait disorder, essential tremor, and drug‐induced parkinsonism as the control group, while excluding idiopathic RBD patients who are considered to be at risk for developing PD, and did not show individual SBRs of the study subjects.…”
Section: Discussionmentioning
confidence: 99%